Poverty and happiness: An examination of the factors influencing happiness among the extreme poor in rural Ghana - Hayford M. Ayerakwa; Robert D. Osei; Isaac Osei-Akoto (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Every person desires some level of inner fulfilment at different stages of life and this could come from a combination of several factors including material and resource acquisition and social prestige. The challenge, however, is whether happiness levels across the different social strata are the same, especially among the poor and the neglected. Using data from the Livelihood Empowerment against Poverty survey in Ghana, we analyse the factors that influence happiness among the extreme poor. The positive and negative factors are discussed in the paper.
Keywords: D04; I38; 330; happiness; poor households; rural Ghana